LEXICAL AND CONTEXTUAL MEANINGS IN “BILLBOARD GLOBAL 200” TOP 1 SONG LYRICS OF 2024: PEDAGOGICAL IMPLICATION - Wimar Amalia, Shabrina; Suwandi, Suwandi; Musarokah, Siti (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This article aims to identify the lexical and contextual meanings in “Billboard Global 200” Top 1 song lyrics of 2024 and to explain the implementation of lexical and contextual meanings for teaching English as a foreign language. The researchers selected three songs that Top 1 in